Kurdish Social Identity in Light of Theories A Theoretical-Analytical Study - عبدالرحیم, سروشت ئەسعەد; Rahim, Dr. Aram Assad Abdul; al-Din, Yahya Karim Saad (Sulaimani Journal for Humanities, 2025)
Humans are social beings who live in societies with their own distinctive cultures that influence them. An individual's personality closely resembles the general character of their society, shaped by institutions like family, school, peer groups, and media that help instil human values and set standards. This research is a theoretical-analytical effort to understand Kurdish social identity from the perspective of sociological theories. The main problem addressed is the lack of specialized theoretical research and limited scientific studies in this field. The research encompasses several key objectives: analysing the concept of Kurdish social identity, identifying and examining the influential factors in identity formation, and interpreting this identity according to sociological theories. The research methodology relies on analysing documents and sociological sources. Through the application of theories of social identity, identity, and ethnicity, the research has reached the following conclusions: Kurdish identity has been formed within a broad social system where roles, norms, and values are constantly changing. It has sometimes faced identity crises, particularly in the modern era when confronting different cultures. The fragmented history of Kurdistan has led to a mixture of identity crisis and place crisis. Kurds, as a national group, have attempted to create positive distinctions with other groups to preserve their identity. Kurdish identity is continuously constructed through daily social experiences, new narratives, cultural developments, and new encounters with the outside world.
Keywords: Identity; Social Identity; Theory